Strategy and Business Process Management - Lehmann, Carl (Auerbach Publications, 2016)
This book prepares readers to master an IT and managerial discipline quickly gaining momentum in organizations of all sizes - Business Process Management (BPM). It describes how BPM treats processes as a portfolio of strategic assets that create and deliver customer and shareholder value and adapt, when necessary, enabling competitive advantage thr.